Relationship between Apnea-Hypopnea Index and Oxygen Desaturation in REM-Sleep Period and Morning Headache in Patients with Obstructive Sleep Apnea Syndrome - KOÇ, Güray (Noro Psikiyatr Ars, 2019)
INTRODUCTION: In patients with morning headache, REM sleep period decreases though little is known about its physiopathology. We evaluate the polysomnographic records of obstructive sleep apnea syndrome (OSAS) patients with the hypothesis that oxygen desaturations may be a better determinant in patients with morning headache, especially those in REM sleep periods. METHODS: Patient group (group 1) with a total of 361 patients with OSAS and the controls (group 2) with 107 healthy individuals were evaluated. The presence of morning headache was compared between the groups, and sleep parameters were correlated with morning headache. RESULTS: In group 1, patients with OSAS and morning headache, apnea-hypopnea index in the REM sleep period (26.7/hour, min-max: 0–108.4/hour) was higher than those in patients without morning headache (17.8/hour, min-max: 0–107.8/hour). The minimum oxygen saturation in REM sleep period and total sleep time (TST) was lower in patients with morning headache (REM sleep period: 82%, min-max: 50–94% ; TST: 79%, min-max: 50–97%) in compared to patients without morning headache (REM sleep period: 84%, min-max: 50–93% ; TST: 81%, min-max: 50–90%). CONCLUSION: Here we demonstrated that higher apnea-hypopnea index and lower oxygen saturation in REM sleep period were associated with morning headache in patients with obstructive sleep apnea syndrome.